Problematika konsultasi kesehatan online (telemedicine) dalam perspektif hukum positif indonesia - Khairunisyah; Adhar; Sahlan; Fitria Binti Masdor S (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study analyzes the issues surrounding online health consultations (telemedicine) from the perspective of Indonesian positive law. The research questions examined in this study include: first, what are the legal policies governing the implementation of telemedicine in Indonesia? and second, what are the legal challenges regarding the protection of personal data, medical malpractice, and the use of digital platforms in telemedicine services in Indonesia?. The research method used in this study is normative legal research. The approaches employed in this study include: a statutory approach, which involves analyzing laws related to telemedicine; and a conceptual approach, which involves reviewing relevant literature and legal doctrines pertaining to the issues under examination. The Research findings indicate that telemedicine regulations in Indonesia remain scattered across various regulations that are not yet fully comprehensive. Some regulations remain general in nature, are limited to services between healthcare facilities, or apply only under specific conditions such as a pandemic. On the other hand, legal challenges in telemedicine include the risk of personal data breaches due to weak system security, difficulties in determining liability in malpractice cases between healthcare providers and platform providers, and the continued lack of oversight over private e-health platforms that often operate outside of health regulations.